Skeletal, dentoalveolar and soft tissue effects of different maxillary expansion appliances in cleft lip/palate patients: A systematic review and frequentist network meta-analysis - Maged S. Alhammadi (14150757) (2025)
Introduction This study aimed to assess the available evidence regarding the skeletal, dentoalveolar, and soft tissue effects of different maxillary expansion appliances in cleft lip/palate patients. Methods We assessed the effects of different maxillary expansion appliances on skeletal and dentoalveolar structures and soft tissues in cleft lip/palate patients. We searched the PubMed, Science Direct, Web of Science, Cochrane, and LILACS databases through September 2024; that investigation was augmented by a manual search. We focused on clinical trials and longitudinal studies, either retrospective or prospective. The outcomes of interest included skeletal, dentoalveolar, and soft tissue changes obtained from study models, cephalometric radiographs, or cone beam computed tomography. Results Of the 430 screened articles, only six satisfied our eligibility criteria and were included in the quantitative synthesis. These articles exhibited a moderate overall risk of bias. None of the appliances conferred better forward skeletal maxillary movement than the hyrax. The iMini-Molars (iMini-M) was the most effective appliance for increasing maxillary skeletal width (mean: 0.89 mm [range: 0.01–1.78]), with the hyrax following closely behind. The Haas appliance exhibited the largest inter-molar distance (mean: 4.76 mm [range: 2.53–6.99]), followed by the Differential opening appliance (EDO), iMini-M, and the hyrax. The fan-type appliance was the least effective at resisting maxillary premolar tipping (14.46° [2.60–26.32]), and the iMini-premolars (iMini-P) was the most effective at reducing molar tipping (-3.54° [-6.06– -1.02]). Conclusions Considering the limited number of studies and moderate risk of bias, the iMini-M was the most effective appliance at increasing maxillary skeletal width compared with the hyrax; the Haas achieved the largest inter-molar distance. The fan-type appliance excelled at resisting premolar tipping, and the iMini-P offered the best control for molar tipping. Registration The protocol for this systematic review was registered at the International Prospective Register of Systematic Reviews (PROSPERO, No.: CRD42023489536) Other Information Published in: Journal of Stomatology Oral and Maxillofacial Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jormas.2025.102312